HUBUNGAN INDEKS PEMBANGUNAN MANUSIA (IPM) DENGAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PER KAPITA DI PROVINSI MALUKU UTARA (SEBUAH ANALISIS TIPOLOGI KLASSEN) - , Kader Noh ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the relationship between the Human Development Index with Gross Regional Domestic Product (GDP) per capita in the Province of North Maluku and analyze the classification of the regency/city in the province of North Maluku based Typology Klassen. Analysis tools in use is the correlation analysis and Typology of Klassen. The results obtained in this study is that there is a significant and positive relationship with Î± = 10 percent of GDP per capita by the Human Development Index regency/city in the province of North Maluku, and There is a significant and positive relationship with Î± = 1 percent between the Gross Regional Domestic Product and the Human Development Index regency/city in the province of North Maluku. Comparison to the respective regency/city by the parameter average Human Development Index (HDI) and GDP per capita of the province between 2005 and 2010, there are three areas that experienced a shift in position, the Central Halmahera quadrant shift up to one in 2010 where in 2005 was in two quadrants